MANAJEMEN PENDIDIKAN MADRASAH ALIYAH BINAAN PESANTREN DALAM PENGEMBANGAN KARAKTER PESERTA DIDIK - Mariyatul Qibtiyah (JURNAL BIMBINGAN DAN KONSELING AR-RAHMAN, 2016)
Educational success is only measured by cognitive domain, and barely measured from affective andpsychomotoric domains, thus fostering character and moral are neglected. There are many youngpeople, pupils and students that can not be expected to become the good skill of human resourcesbut they are to be a burden of development. The aim of this research is to formulate a conceptualmodel of educational management of character development. The research method is descriptivemethod. Locations of the research are MA Salafiyah Syafiiyah Tebuireng Jombang, MA Nurul JadidPaiton Probolinggo and MA Darusshulah Jember. The procedure of this research through threephases: orientation studies, general exploration and exploration centered. In this study theresearcher herself as a key instrument in collecting primary data and secondary data. Techniques ofdata collection through: in-depth interviews, participant observation and documentation studies.The research results showed that the planning is done to internalize the character values in theformulation of the vision, mission, objectives, syllabus and lesson plans and the entire program ofactivities that lead to the formation of character. Organizing done through the delegation of tasksbased on skill and profession of each teacher in various seminars, MGMP and workshops.Implementation of education are implemented integratedly among intra-curricular activities, extracurricularand pesantren activities. The strategy emphasizes the exemplary education, habituationand parenting. The principles taught in instilling character are through the process of knowledge(knowing), do (doing) and finally to familiarize (habituation). Assessment is done through programassessment, process and outcome. Output generated the character of learners. The Conclusion are;The success of the MA in planting character values can not be separated from the role of kyai,institutional leaders and chaplains (ustadz) in providing role models and guidance to the learnersto put it mildly solely seek the blessing of Allah, besides influenced by education managementdevelopment of good character, and values of best practices developed in pesantren throughhabituation life or ro'an mutual cooperation, brotherhood, freedom of thought, simplicity of life,independence and akhlakul karimah. Recommendations to the pesantren leaders, headmaster,teachers and education to continuously improve the development of character educationmanagement better. To the head of the government it is time to give attention to a balanced and fairMA significantly assisted pesantren has managed to produce graduates who are more character(noble).